Psychiatric Assistance at Cataract Juvenile - I Gusti Ayu Indah Ardani; Yunias Setiawati; Joni Wahyuhadi (Health Notions, 2019)
Background: Psychiatric assistance is required in the integrated handling of physical health disorders in the field of other disciplines known as CLP. A collaborative approach to the field of psychiatry with other scientific disciplines in accordance with WHO health criteria that includes physical and mental health for improving health and quality of life. Case presentation: A boy, 8 years, was consulted from the Ophthalmology Department with Right eye cataract juvenile, and left eye ptisis bulbi to give pre-operative psychological assistance for eye assessment and diagnostics. Patient also complained the blurred vision since last year and cannot see anything since 10 months ago. The current condition represents the patient cannot speak, often screams, likes to injure his head and scratch his face. Patients treated in the pediatric’s ward with global developmental delay. Patients were also consulted to the child psychiatry section with childhood autism, audiology, nutrition and metabolic diseases of children, pediatric neurology, and finally collaboration with the Surabaya City Health Office for a follow-up management plan. Conclusions: Child psychiatrist as a liaison, interacting with multidisciplinary medical or rehabilitation teams, families, schools, community and local city government are beneficial in the management of child disorders and improving family wellbeing. Keywords: cataract juvenile; autism; psychiatric assistance; consultation liaison psychiatry (CLP)